Comparative analysis of salt responsive gene regulatory networks in rice and Arabidopsis. (April 2020) - Wang, Rui; Cheng, Yanhao; Ke, Xiaojuan; Zhang, Xiaofan; Zhang, Hongsheng; Huang, Ji
Graphical abstract: Highlights: Based on public salt –related microArray data, small RNA-seq and degradome sequence, we constructed and compared salt-response networks in rice and Arabidopsis, consisting of miRNAs, genes and transcription factors (TFs). In rice, more target genes of networks were enriched in development and growth, while more stress directly-related genes were detected in Arabidopsis networks. Salt response networks of Arabidopsis are typically organized. Salt-response mechanisms of rice are emphasized on avoiding salt stress by regulating growth and development according to rice miRNA-TF-genes networks. MiRNA171-GRAS and miRNA169-NFYA are possible species-conserved salt-response patterns. Not only are they detected in our results, but also reported in other signaling pathways. For instance, miRNA169-NFYA is found work in ABA signaling pathways. Abstract: By using the available expression datasets of mRNAs and small RNAs, we constructed and compared the salt-responsive gene regulatory networks (GRNs) involving both transcriptional and post-transcriptional regulations between model plants rice and Arabidopsis. The salt-responsive GRNs involve the transcription factors (TFs), microRNAs (miRNAs) and their target genes. Here we describe 552 miRNA-target interactions (MTIs), 95 up-regulated TF-target interactions (TTIs) and 56 down-regulated TTIs in rice, while 332 MTIs, 138 up-regulated and 4 down-regulated TTIs in Arabidopsis. Interestingly, we observed the networks in rice are more complicated where target genes were enriched in rice development and growth, while more stress-related genes were detected in Arabidopsis networks. With the construction and comparison of GRNs between rice and Arabidopsis in response to salt stress, we can basically describe the differences of salt responsive mechanisms in two species: rice tends to respond slower and chooses to manipulate its development and growth to avoid salt stress, while Arabidopsis prefers to trigger a serious salt-defending genes to protect itself from stress. Our work provides the foundation for further exploring the molecular basis of plant salt response and the potential breeding practice by engineering the critical components in the networks in improving plant salt tolerance.